Optimization and Thermoeconomics Research of a Large Reclaimed Water Source Heat Pump System. (5th September 2013) - Zhang, Zi-ping; Du, Fang-hui
Abstract : This work describes a large reclaimed water source heat pump system (RWSHPS) and elaborates on the composition of the system and its design principles. According to the characteristics of the reclaimed water and taking into account the initial investment, the project is divided into two stages: the first stage adopts distributed heat pump heating system and the second adopts the combination of centralized and decentralized systems. We analyze the heating capacity of the RWSHPS, when the phase II project is completed, the system can provide hydronic heating water with the supply and return water temperature of 55°C/15°C and meet the hydronic heating demand of 8 million square meters of residential buildings. We make a thermal economics analysis by using Thermal Economics theory on RWSHPS and gas boiler system, it is known that the RWSHPS has more advantages, compared with the gas boiler heating system; both its thermal efficiency and economic efficiency are relatively high. It provides a reference for future applications of the RWSHPS.